SOCIOLINGUISTICS STUDY ON THE USE OF SOCIOLINGUISTICS STUDY ON THE USE OF PROVERBS AND ROUTINE LINGUISTIC SMALL TALK IN THE MINANGKABAU COMMUNITY - Salliyanti, Salliyanti; Susilo, Hariadi; Bangun, Pribadi (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2023)
This research was field research entitled "Sociolinguistic Study of the Use of Proverbs and Routine Linguistic Small Talks in Minangkabau Society in the Bromo area of Medan". The problem discussed was the use of proverbs and their meanings as well as routine linguistic small talks or chit-chat used by the Minangkabau community in the Bromo Medan area. The purpose of this study aimed at exploring or introducing regional culture because it is part of national culture to the younger generation because so far, it has not talked much about the routine use of proverbs and linguistic small talk by describing their uses. To analyze the use of the proverb as well as the meaning and use of these small talks which are used in the Minangkabau community in the Bromo area, a sociolinguistic study was applied which referred to the views of Abdul Chaer and Sumarsono and Krida Laksana. The method used in data collection was the listening method by listening to the conversation of the informants about the proverb, small talk, and its meaning. Then proceed with speaking techniques and conversational engagement techniques which researchers were involved in. The method used to analyze the data was the equivalent method. The method used to analyze the data is the equivalent method (Sudaryanto, 1993:13). Furthermore, the researcher also applied the descriptive qualitative method. That is, this analysis as a whole utilizes the ways of interpretation presented in the form of a description. The results of the analysis in this discussion were proverbs and small talk by showing their meaning such as that life must be wise, the proverb for learning, the proverb of the firm and wise, the proverb of culture that is eroded, the proverb of regret, the proverb of advice, and the proverb of frugality. Furthermore, there was also the use of routine linguistic small talk such as small talk in a meeting, saying goodbye, receiving something, giving something, improving the atmosphere, mourning, cursing or swearing, advising, and prohibiting. By showing moral values in using proverbs and using small talk language in the Bromo area of Medan city, the most dominant small talk used were small talk in a meeting, condolences, and prohibiting